Semiconducting Polymer Nanoparticles with Surface‐Mimicking Protein Secondary Structure as Lysosome‐Targeting Chimaeras for Self‐Synergistic Cancer Immunotherapy. Issue 31 (5th July 2022) - Qi, Ji; Jia, Shaorui; Kang, Xiaoying; Wu, Xinying; Hong, Yuning; Shan, Ke; Kong, Xianglong; Wang, Zhiming; Ding, Dan
Abstract: Immunotherapy has received tremendous attention for tumor treatment, but the efficacy is greatly hindered by insufficient tumor‐infiltration of immune cells and immunosuppressive tumor microenvironment. The strategy that can efficiently activate cytotoxic T lymphocytes and inhibit negative immune regulators will greatly amplify immunotherapy outcome, which is however very rare. Herein, a new kind of semiconducting polymer (SP) nanoparticles is developed, featured with surface‐mimicking protein secondary structure (SPSS NPs) for self‐synergistic cancer immunotherapy by combining immunogenic cell death (ICD) and immune checkpoint blockade therapy. The SPs with excellent photodynamic property are synthesized by rational fluorination, which can massively induce ICD. Additionally, the peptide antagonists are introduced and self‐assembled into β‐sheet protein secondary structures on the photodynamic NP surface via preparation process optimization, which function as efficient lysosome‐targeting chimaeras (LYTACs) to mediate the degradation of programmed cell death ligand‐1 (PD‐L1) in lysosome. In vivo experiments demonstrate that SPSS NPs can not only elicit strong antitumor immunity to suppress both primary tumor and distant tumor, but also evoke long‐term immunological memory against tumor rechallenge. This work introduces a new kind of robust immunotherapy agents by combining well‐designed photosensitizer‐based ICD induction and protein secondary structures‐mediated LYTAC‐like multivalence PD‐L1 blockade, rendering great promise for synergistic immunotherapy. Abstract : A new kind of photodynamic semiconducting polymer nanoparticles with surface mimicking protein secondary structure (SPSS NPs) is developed to achieve self‐synergistic cancer immunotherapy by combining excellent immunogenic cell death and lysosome‐targeting chimaera‐like multivalent programmed cell death ligand‐1 blockade. SPSS NPs can not only effectively suppress both primary tumor and distant tumor, but also evoke long‐term immunological memory against tumor rechallenge.